1984
DOI: 10.1139/f84-020
|View full text |Cite
|
Sign up to set email alerts
|

Hypolimnetic Aeration and Zooplankton Distribution: A Possible Limitation to the Restoration of Cold-Water Fish Production

Abstract: One. ha38 1P3 Taggart, C. 8. 1984. Hypolimnetic aeration and zooplankton distribution: a possible limitation to the restoration of cold-water fish production. Can. I. Hypolimnetic aeration of a 1.23-ha eutrophic kettle lake during two consecutive summers increased [Qzl to more than 4m@L in the hypolimnion for extended periods. This improvement did not lead to the expected development of crustacean populations in the previously anoxic, zooplankton-deficient hypo. Bimnion. The rotifer Fdinia longiseta was the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 15 publications
0
8
0
3
Order By: Relevance
“…Shapiro and Wright (1984) were unable to establish a DO refuge since quantities of oxygen injected into the metalimnion could not compensate for the high BOD in Round Lake, Minnesota, USA. Despite hypolimnetic aeration throughout the summer of a small kettle lake in Ontario, Canada, high BOD resulted in anoxia after mid-July or August in the hypolimnion; hydrogen sulfide accumulated in the metalimnion and restricted zooplankton to the epilimnion (Taggart 1984). Successful establishment of a DO refuge will likely only occur when internal cycling of phosphorus and external nutrient loading are reduced.…”
Section: Refuge Establishmentmentioning
confidence: 99%
“…Shapiro and Wright (1984) were unable to establish a DO refuge since quantities of oxygen injected into the metalimnion could not compensate for the high BOD in Round Lake, Minnesota, USA. Despite hypolimnetic aeration throughout the summer of a small kettle lake in Ontario, Canada, high BOD resulted in anoxia after mid-July or August in the hypolimnion; hydrogen sulfide accumulated in the metalimnion and restricted zooplankton to the epilimnion (Taggart 1984). Successful establishment of a DO refuge will likely only occur when internal cycling of phosphorus and external nutrient loading are reduced.…”
Section: Refuge Establishmentmentioning
confidence: 99%
“…McQUEEN et STORY (1986) affirmèrent que la composition et la succession du phytoplancton n'étaient pas modifiées par l'aération, et que la biomasse et la productivité primaire augmentaient ou ne variaient pas. TAGGART (1984) observa qu'aucune recherche sur l'effet de l'aération sur le zooplancton n'avait été publiée avant 1984, et McQUEEN et STORY (1986 ne trouvèrent que cinq articles sur ce sujet. Ces auteurs conclurent de leur expérience que l'influence de l'aération sur le zooplankton était négligeable.…”
Section: Discussion Et Conclusionunclassified
“…Il fut donc décidé -avant d'appliquer cette méthode au lac tout entier -d'effectuer deux expériences au moyen de la méthode de 1*"enceinte". Des enceintes furent utilisées dans le même but par d'autres auteurs (par exemple, McQUEEN et LEAN, 1983, 1984McLEAK et STORY, 1986). Nous avons réalisé deux expériences : l'une du 26 septembre au 9 décembre 1986, l'autre du 22 avril au 30 novembre 1987.…”
Section: Introductionunclassified
“…Like Ashley (1), we observed higher summer-fall cyclopoid populations in the aerated enclosure, but unlike him, the calanoid populations in both enclosures were very similar. Taggart (30), found that a metalimnetic barrier comprising low concentrations of DO and high concentrations of hydrogen sulfide resulted in zooplankton populations that were restricted to the epilimnion. The exception was Filinia longiseta which was found in the hypolimnion.…”
Section: Zooplanktonmentioning
confidence: 99%